Overconfidence CEO dan Nilai Perusahaan: Peran Mediasi Struktur Modal dan Investasi - Akhmad Yani; Riris Rotua Sitorus (Owner : Riset dan Jurnal Akuntansi, 2025)
This study evaluates the impact of CEO overconfidence on company value, with the mediating role of capital structure and investment policy. The background of this study is highly relevant given the increasing attention to psychological aspects in financial decision-making in emerging markets, such as Indonesia, where leadership dynamics play an important role in business strategy and company value fluctuations. CEO overconfidence can encourage bold decision-making, which has the potential to increase company value. However, this behavior can also pose significant risks if not managed properly. The study uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) techniques to analyze 450 observations from 90 companies in the raw materials, consumer goods, energy, infrastructure, and manufacturing sectors listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The CEO overconfidence index was measured through a combination of demographic indicators such as share ownership, age, tenure, and education level. The analysis results show that CEO overconfidence has a significant effect on capital structure and investment policy, as well as a direct impact on company value. Of the two mediating variables, only investment policy (ROI) significantly mediates this relationship, while capital structure (DER) does not. These findings support behavioral finance theory and signaling theory, which affirm that cognitive biases play a real role in managerial financial decisions. Practically, this study provides important insights for investors to evaluate the impact of psychological biases on company performance and for boards of directors to formulate incentive policies that can manage CEO behavioral risks, thereby making strategic decision-making more optimal and transparent.